Study of The Use of Composite Flour Waste of Bean Sprouts Skin with Ganyong Flour (Canna edulis Kre.) Against The Characteristics of Probiotic Biscuit - Florentina Dwi Putri; Indira Lanti Kayaputri; Heni Radiani Arifin (Journal of Industrial and Information Technology in Agriculture, 2018)
The skin of bean sprouts is a waste in the process of green beans into sprouts, while ganyong is a typical local tuber of west java which is very rarly used. Waste of bean sprouts has high fiber and protein content, while ganyong has high carb content. Both raw materials have potential to be processed into a probiotics biscuit products. Biscuit probiotics is a biscuit that has a probiotic content that is instrumental in human body digestion. This research aims to set the offset of composite waste skin of bean sprouts and ganyong flour with good characteristic and liked by the panelist. Research method are conduct experimental by using random block design continued with Duncan test. The treatment used is a variety of formula waste skin of bean sprouts flour (TLKT) : ganyong flour (TG : flour (TT); (P1) 20%:60%:20%, (P2) 30%:50%:20%, (P3) 40%:40%:20% against the total weight of biscuit probiotics dough. The source of probiotic is obtained from adding freeze dried culture in mother culture form. Probiotic biscuits’ organoleptic characteristic were testing through hedonic test by 15 semi-trained panelist. Research results shows the difference of those TLKT and TG gives a real different influence against taste, but give not real different against color, aroma, visibility, texture, after taste of probiotic biscuit. Probiotic biscuit formula P2 (30% TLKT:50% TG) selected as the best treatment also liked a bit by the panelist. Keywords: freeze dried, ganyong flour, probiotic biscuit, skin waste of bean sprouts flour